Развтитие частотного плана DWDM систем на основе излучения фемтосекундного лазера - Мачехин, Ю. П.; Вознюк, Е. П. (ХНУРЭ, 2008)
The results of research of possibility of application of femtosecond laser is investigational in DWDM systems, with the purpose of replacement of discrete semiconductor sources of light and increase of volumes of transferrable information.
Keywords: фемтосекундный лазер; DWDM система